2015
DOI: 10.1128/jvi.01588-15
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the Human Papillomavirus Minor Capsid Protein L2 during Vesicular Trafficking of Infectious Entry

Abstract: The human papillomavirus (HPV) capsid is composed of the major capsid protein L1 and the minor capsid protein L2. During entry, the HPV capsid undergoes numerous conformational changes that result in endosomal uptake and subsequent trafficking of the L2 protein in complex with the viral DNA to the trans-Golgi network. To facilitate this transport, the L2 protein harbors a number of putative motifs that, if capable of direct interaction, would interact with cytosolic host cell factors. These data imply that a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 64 publications
(86 reference statements)
5
89
0
Order By: Relevance
“…Regardless, our data suggest that the L2 protein is important for directing the HPV-containing membranous structures toward the nucleus during mitosis. It was recently demonstrated that the L2 protein becomes transmembranous to engage numerous cytoplasmic factors required for trafficking to the TGN and possibly the ER, with some 30 N-terminal residues being luminal (28,32). We have shown that L2 assumes a similar topography during mitosis, suggesting that HPV-harboring vesicles bud out of the TGN or the ER during the onset of mitosis.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Regardless, our data suggest that the L2 protein is important for directing the HPV-containing membranous structures toward the nucleus during mitosis. It was recently demonstrated that the L2 protein becomes transmembranous to engage numerous cytoplasmic factors required for trafficking to the TGN and possibly the ER, with some 30 N-terminal residues being luminal (28,32). We have shown that L2 assumes a similar topography during mitosis, suggesting that HPV-harboring vesicles bud out of the TGN or the ER during the onset of mitosis.…”
Section: Discussionmentioning
confidence: 72%
“…As reported previously, the L2-specific antibodies show a high level of background even in uninfected cells, along with a low signal intensity (32). In addition, the antibodies are large macromolecules of ∼150 kDa and have limited accessibility for proteins present in larger complexes.…”
Section: Significancementioning
confidence: 74%
See 3 more Smart Citations